2005
DOI: 10.1191/0960327105ht527oa
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of poisoning cases reported to the National Poisons Information Centre, All India Institute of Medical Sciences, New Delhi

Abstract: A retrospective analysis of poisoning calls received by the National Poisons Information Centre showed a total of 2719 calls over a period of three years (April 1999-March 2002). The queries were made on poisoning management (92%) and information (8%) about various products and functioning of the centre. The data were analysed with respect to age, sex, mode and type of poisoning. The agents belonged to various groups: household products, agricultural pesticides, industrial chemicals, drugs, plants, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
128
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 26 publications
23
128
3
3
Order By: Relevance
“…(1-68years) to that reported from AIIMS (Srivastava et al 6 In our study, the total dose of PAM required ranged from 4-48gm with mean dose of 24.22gm and the duration of PAM administration was 1-8 days.…”
Section: Discussionsupporting
confidence: 55%
“…(1-68years) to that reported from AIIMS (Srivastava et al 6 In our study, the total dose of PAM required ranged from 4-48gm with mean dose of 24.22gm and the duration of PAM administration was 1-8 days.…”
Section: Discussionsupporting
confidence: 55%
“…Zatruciom częściej ulegali mężczyźni niż kobiety, co jest zbieżne z ustaleniami innych autorów [13,14]. Wynika to głównie z rosną-cej odpowiedzialności za rodzinę, stresu zawodowego oraz konfliktów w relacjach z innymi, co prowadzi do lęków egzystencjalnych i skłonności samobójczych [1,[15][16][17][18]. Nasilający się stres jest głównym czynnikiem w przypadku zatruć umyślnych.…”
Section: Discussionunclassified
“…It is mainly due to increasing responsibility in family; stress related to the jobs and conflict in relations which overall leads to a condition of grief for existence and suicidal tendency [1,[15][16][17][18]. The increasing stress is a chief factor for intentional poisoning whereas unhealthy practices or risk taking behaviors in individual are mainly responsible for unintentional poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the reason of having drug poisonings more might be related with having suicidal poisoning cases more. Studies have reported that the ratio of suicidal poisonings in cases presenting to hospitals with poisoning varies between 47% and 97% [11,17,18].…”
Section: Discussionmentioning
confidence: 99%